The Influence of PLN Empowered Village Innovation on Capacity HR in Manistutu Village, Jembrana Regency, Bali - I Made Arya; Komang Agus Rudi Indra Laksmana; Wayan Ardani; Ni Luh Ketut Ayu Sudha Sucandrawati (International Journal of Economics, Business and Innovation Research, 2026)
This study investigates the impact of the "Desa Berdaya PLN" innovation on human resource capacity in Manistutu Village, Bali, utilizing a sequential explanatory mixed-methods design to evaluate the program's shift from traditional Corporate Social Responsibility (CSR) to Creating Shared Value (CSV). The research employs Structural Equation Modeling-Partial Least Squares (SEM-PLS) to analyze quantitative data from program beneficiaries, followed by in-depth interviews to contextualize the findings. The results demonstrate that the innovation program has a positive and significant direct effect on community knowledge, skills, and superior competence, with knowledge and skill enhancement serving as a crucial mediator in this relationship. Conclusively, the study affirms that integrating energy infrastructure with structured capacity-building effectively transforms rural human capital, though sustainable empowerment requires further addressing market access and strengthening local institutional governance